MOKSA AND THE MEANS OF ITS ATTAINMENT IN KASHMIR SAIVISM - Hughes, John (Journal of Dharma, 1995)
The Sanskrit word mokse is commonly translated in English as spiritual "liberation" or "freedom." With some exceptions in the bhakti traditions it is held by all of the great philosophical and religious tra- ditions of India to be the true and fitting purpose of all human endea- vor. Although these traditions teach that the attainment of. this hu- man emancipation is the end all and be all of spiritual life, they have quite different interpretations of what this term actually means. In fact, there are as many different interpretations of the meaning of moks« as there are philosophical understandings about the nature of God and the world. And, as the various schools differ in their understanding of the nature of mokss, so also do they differ in regard to the means (upaya) by which it is to be attained.